A nickel complex with a biscarbene pincer-type ligand shows high electrocatalytic reduction of CO2 over H2O1. Issue 37 (7th October 2015) - Sheng, Meili; Jiang, Nan; Gustafson, Samantha; You, Bo; Ess, Daniel H.; Sun, Yujie
<x xml:space="preserve">Abstract</x> We report a planar nickel complex coordinated with a pincer-type carbene–pyridine–carbene ligand which exhibits high selectivity for electrocatalytic CO2 reduction in the presence of H2O.